ENGLISH LANGUAGE LEARNING STRATEGIES: ATTEND TO FROM AND ATTEND TO MEANING STRATEGIES (A CASE STUDY AT SMA NEGERI 9 MAKASSAR) - Weda Sukardi (Institut Agama Islam Negeri Palopo, 2014)
This study examines the most dominant of the English Language Learning Strategies (ELLSs) employed by secondary school students in Indonesia, and the relationship between language learning strategies (LLSs) use and students English proficiency level. The main instrument used was a 26-item Inventory of Language Learning Strategies by Good Language Learners (GLL) developed by Rubin which was conducted on 85 students from two classes which focused on social sciences at secondary school. Data analysis relied heavily on statistical analysis i.e., Multiple Comparison Tests. The results of the study revealed that the most dominant (popular) of English Language Learning Strategies (ELLSs) used by secondary school students was Attend to Form and Attend to Meaning, and others were the least popular, and the students who employed various strategies had good scores in the test. This revealed that language learning strategies facilitate the learning of English as a foreign language (EFL) in Indonesia.